PENURUNAN BOD DAN COD LIMBAH CAIR INDUSTRI TAPIOKA DI KABUPATEN PURBALINGGA DENGAN METODE PELAPISAN TANAH BERGANDA DECREASING BOD AND COD OF TAPIOCA INDUSTRIAL LIQUIDWASTE AT PURBALINGGA REGENCY BY MULTI SOIL LAYERING METHOD - , Suyata; , Irmanto; , Warsinah (Pembangunan Pedesaan, 2006)
Multi Soil Layering (MSL) method for decreasing BOD (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand) of tapioca industrial liquidwaste at Purbalingga has been developed. MSL is a method of liquidwaste treatment enhancing function of soils to purify the waste. The research aimed at determining optimum loading rate and efficiency of MSL system to decrease BOD and COD. Results showed that optimum loading rate of the waste to the system was 320 L m- 2day-1 and efficiency of the system to decrease BOD and COD was 94.50 and 91.50%, respectively. Keywords: Multi Soil Layering method, Tapioca industrial liquidwaste, BOD, COD.